The Value of Interactive Assignments in the Online Learning Environment. Issue 3 (1st September 2016) - Florenthal, Bela
Abstract : The offerings of Web-based supplemental material for textbooks have been increasingly growing. When deciding to adopt a textbook, instructors examine the added value of the associated supplements, also called e-learning tools, to enhance students' learning of course concepts. In this study, one such supplement, interactive assignments, is examined from students' perspective. Two steams of literature, information technology and communication, provide the foundation to understanding students' evaluation of the interactive assignments. The results of the study indicate that the motivational theory of uses and gratification contributes significantly to our understanding of students' perceived value of, attitude toward, and satisfaction from completing e-learning assignments. Also contributing to our understanding are the concepts of results demonstrability and conformation of expectation, which have been adopted from the literature related to the technology acceptance model. Implications for publishers and instructors are provided.